Thermal Diffusion and Mass Transfer Effects on MHD Flow of a Dusty Gas through Porous Medium. (8th February 2012) - Kumar, Rajesh; Kumar, Devendra; Shrivastav, R. K.
Abstract : The present problem is concerned with the thermal diffusion mass transfer effects on MHD free convective flow of dusty gas through a porous medium induced by the motion of a semi-infinite flat plate moving with velocity decreasing "exponentially with time". The effects of various parameters like magnetic parameter M thermal diffusion effect as soret number S 1, permeability parameter K 1, Schimdt number S c are taken into account. The velocity profile, temperature field, and concentration of incompressible dusty gas and dust particles for several parameters are discussed numerically and explained graphically.